Evaluating the Impact of Thermal Processing on the Anti-Inflammatory Activity of Non-Centrifugal Cane Sugar: Implications on Cytokine Secretion and TLR4 Signaling - Rueda-Gensini, Laura; Serna, Julian A.; Bolaños, Natalia I.; Rodriguez, Jader; Cruz, Juan C.; Muñoz-Camargo, Carolina (Frontiers in Pharmacology, 2022)
Plant-derived products have gained considerable attention as inflammation modulators given the wide variety of anti-inflammatory phytochemicals reported to be present in plants and their limited side effects in vivo during prolonged exposure periods. Non-centrifugal cane sugar (NCS) has been identified as a promising sugarcane-derived product due to its high polyphenolic composition and antioxidant potential, but its incorporations into nutraceuticals and other relevant products of biomedical interest has been limited by the ample composition-wise variability resulting from extreme and loosely controlled processing conditions. Here, we assessed the effect of reducing thermal exposure during NCS processing on the retained polyphenolic profiles, as well as on their antioxidant and anti-inflammatory activities. Specifically, we proposed two modified NCS production methods that reduce exposure to unwanted thermal processing conditions by (i) limiting the employed temperatures through vacuum-aided dehydration and (ii) by reducing exposure time through refractance window evaporation. By comparing the modified NCS products with traditional NCS, we showed that the proposed process strategies yield enhanced polyphenolic profiles, as evidenced by the results of the Folin-Ciocalteu polyphenol quantification method and the components identification by HPLC coupled to mass spectrometry. Although these compositional differences failed to impact the antioxidant profiles and cytocompatibility of the products, they showed an enhanced anti-inflammatory potential, given their superior modulation capacity of inflammatory cytokine secretion in both systemic and neuroinflammatory scenarios in vitro. Moreover, we showed that both modified NCS products interfere with TLR4 signaling in human monocytes to a significantly greater extent than traditional NCS. However, the anti-inflammatory effect of NCS produced under window refractance evaporation was slightly superior than under vacuum-aided dehydration, demonstrating that reducing exposure time to high temperatures is likely more effective than reducing the operation temperature. Overall, these findings demonstrated that limiting thermal exposure is beneficial for the development of NCS-based natural products with superior anti-inflammatory potential, which can be further exploited in the rational design of more potent nutraceuticals for potentially preventing chronic inflammatory diseases.